Tingkat Literasi Perpajakan pada Anggota PKK RW 019, Kecamatan Bekasi Barat - Kurniasih, Novie; Rahmawati, Suci; Wulandari, Putri Riski; Pratama, Firzian Arie; Fatimah, Ina Siti; Lathifah, Fidela; Nuri, Fayi Evan; Zahra, Salma Esvania; Faradysa, Ananda Lingga; Wicaksono , Syafiq; Putra, Adam Febrian (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to measure the level of tax literacy among members of the PKK (Family Welfare Program) in RW 019, West Bekasi District. The methodology employed includes surveys, direct material delivery, simulations, and discussions on tax literacy and tax compliance in the context of civic duty. The results of this activity are expected to enhance the understanding of PKK members regarding tax compliance, particularly in addressing misuses of taxes both personally and within families, enabling them to be more responsive in understanding and mitigating tax-related issues in the future. Additionally, tax understanding is crucial for Generation Z, as knowledge of tax regulations, functions, systems, and types of taxes is highly relevant. Through this activity, the community is expected to manage their tax obligations more effectively.